Update on Salivary Gland Fine-Needle Aspiration and the Milan System for Reporting Salivary Gland Cytopathology. - Pusztaszeri, Marc; Rossi, Esther Diana; Faquin, William C. (Archives of Pathology & Laboratory Medicine, 2024)
Context.--Fine-needle aspiration (FNA) is a well-established procedure for the diagnosis and management of salivary gland lesions, despite challenges imposed by salivary gland tumor diversity, complexity, and cytomor-phologic overlap. Until recently, the reporting of salivary gland FNA specimens was inconsistent among different institutions throughout the world, leading to diagnostic confusion among pathologists and clinicians. In 2015, an international group of pathologists initiated the development of an evidence-based tiered classification system for reporting salivary gland FNA specimens, the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC). The MSRSGC consists of 6 diagnostic categories, which incorporate the morphologic heterogeneity and overlap among various nonneoplastic, benign, and malignant lesions of the salivary glands. In addition, each MSRSGC diagnostic category is associated with a risk of malignancy and management recommendations. Objective.--To review the current status of salivary gland FNA, core needle biopsies, ancillary studies, and the beneficial role of the MSRSGC in providing a framework for reporting salivary gland lesions and guiding clinical management. Data Sources.--Literature review and personal institutional experience. Conclusions.--The main goal of the MSRSGC is to improve communication between cytopathologists and treating clinicians, while also facilitating cytologic-histo-logic correlation, quality improvement, and research. Since its implementation, the MSRSGC has gained international acceptance as a tool to improve reporting standards and consistency in this complex diagnostic area, and it has been endorsed by the 2021 American Society of Clinical Oncology management guidelines for salivary gland cancer. The large amount of data from published studies using MSRSGC served as a basis for the recent update of the MSRSGC.